Charge-assisted phosph(v)azane anion receptors. Issue 11 (4th March 2020) - Plajer, Alex J.; Lee, Sanha; Bond, Andrew D.; Goodman, Jonathan M.; Wright, Dominic S.
Abstract : Cationic metal and non-metal based phosph(v )azane receptors have enhanced anion affinity compared to neutral phosph(v )azane arrangements. Abstract : Coordination of Cu(i ) or Pd(ii ) to seleno-cyclodiphosph(v )azanes of the type [RNH(Se)P(μ-N t Bu)]2 results in positively charged anion receptor units which have increased anion affinity over the neutral seleno-phosph(v )azanes, due to the increase in electrostatic interactions between the receptor and the guest anions. The same effect is produced by replacement of one of the PSe units by a P–Me + unit.